Neural Correlates of Subjective Awareness for Natural Scene Categorization of Color Photographs and Line-Drawings - Fu, Qiufang; Liu, Yong-Jin; Dienes, Zoltan; Wu, Jianhui; Chen, Wenfeng; Fu, Xiaolan (Frontiers in Psychology, 2017)
It remains controversial whether visual awareness is correlated with early activation indicated by VAN (visual awareness negativity), as the recurrent process hypothesis theory proposes, or with later activation indicated by P3 or LP (late positive), as suggested by global workspace theories. To address this issue, a backward masking task was adopted, in which participants were first asked to categorize natural scenes of color photographs and line-drawings and then to rate the clarity of their visual experience on a perceptual awareness scale (PAS). The interstimulus interval (ISI) between the scene and the mask was manipulated. The behavioral results showed that categorization accuracy increased with PAS ratings for both color photographs and line-drawings, with no difference in accuracy between the two types of images for each rating, indicating that the experience rating reflected visibility. Importantly, the ERP results revealed that for correct trials, the early posterior N1 and anterior P2 components changed with the PAS ratings for color photographs, but did not vary with the PAS ratings for line-drawings, indicating that the N1 and P2 do not always correlate with subjective visual awareness. Moreover, for both types of images, the anterior N2 and posterior VAN changed with the PAS ratings in a linear way, while the LP changed with the PAS ratings in a nonlinear way, suggesting that these components relate to different types of subjective awareness. The results reconcile the apparently contradictory predictions of different theories and help to resolve the current debate on neural correlates of visual awareness.